Burden of serious fungal infections in the Dominican Republic - Harish C. Gugnani; David W. Denning (Elsevier, 2016)
Summary: The Dominican Republic (DR) is the second largest Caribbean nation and, with Haiti, the DR accounts for nearly three-quarters of the cases of human immunodeficiency virus (HIV) infection in the Caribbean region and the highest rates of TB in the Americas. The present study estimated the burden of serious fungal infections and some other mycoses in the DR. The data were extracted from the World Health Organization Stop Tuberculosis (WHO STOP TB) program, the Joint United Nations Program on HIV/AIDS (UNAIDS), and searches for relevant literature via MEDLINE, PubMed, MedFacts, and so on. The chronic pulmonary aspergillosis (CPA), allergic bronchopulmonary aspergillosis (ABPA), and severe asthma with fungal sensitization (SAFS) rates were derived from the asthma and TB rates. When no data regarding mycoses were available, we used specific populations at risk and the frequencies of fungal infection in each of these populations to estimate the national prevalence. Among its population of 10,090,000, we estimated that 221,027 (2.2%) have a serious fungal infection, including 158,134 women with recurrent vulvovaginal candidiasis. We estimated high numbers of 25,150 for ABPA and 34,000 for severe asthma fungal sensitization (SAFS) (250 and 529/100,000, respectively). CPA was common, with an estimated 2122 cases, of which 707 followed pulmonary TB. The annual prevalence of CPA was estimated to be 1374 cases. Four cases of histoplasmosis and several cases of chromoblastomycosis have also been reported. Pityriasis versicolor and tinea capitis are frequent in children, and 11% have kerion. Local epidemiological investigations are urgently required to validate or modify these estimates of serious fungal infections in the DR. Keywords: Mycoses, Histoplasmosis, Cryptococcosis, Pneumocystosis, Aspergillosis